Evaluation of total urethral thickness using ultrasonography in cats - Lee, Seungeun; An, Yoojin; Choi, Yoonju; Kim, Sungsoo; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2025)
IntroductionUrethral wall thickness is a potential indicator of pathological changes in the feline lower urinary tract. However, reference values for total urethral thickness in cats have not been established. This study aimed to develop ultrasonographic reference ranges for total urethral thickness in clinically normal cats and to evaluate the effects of breed, sex, neutering status, body weight, and bladder volume. We further compared urethral thickness between healthy cats and those presenting with lower urinary tract signs (LUTS) and determined a diagnostic cutoff value.MethodsA total of 302 cats were retrospectively analyzed in a multicenter study. Measurements were obtained from mid-sagittal ultrasonographic images at the level cranial to the pelvic symphysis.ResultsIn clinically normal cats (n = 240), mean total urethral thickness was 2.20 ± 0.26 mm, with no significant influence of sex, breed, body weight, or bladder volume. Cats with LUTS (n = 62) demonstrated significantly greater urethral thickness (2.75 ± 0.51 mm, p < 0.001). Multivariable analysis identified LUTS as the strongest independent predictor of increased urethral thickness. Receiver operating characteristic analysis yielded an area under the curve of 0.859, confirmed by bootstrap validation (bias-corrected AUC = 0.858; 95% CI: 0.7840.918). A diagnostic cutoff of 2.49 mm achieved 76% sensitivity and 88% specificity.DiscussionThese findings establish ultrasonographic reference ranges for feline urethral thickness and propose a clinically useful threshold for detecting urethral abnormalities. Ultrasonography may therefore provide a reliable, non-invasive tool for evaluating urethral pathology in cats.